Building an African Leptospirosis Network - Benschop, J.; Allan, K.; Fayaz, A.; Bastos, A.D.S.; Collins-Emerson, J.; Crump, J.A.; Dobigny, G.; El Azhari, M.; El-Tras, W.F.; Halliday, J.; Koffi, S.K.; Lindahl, Johanna F.; et al. (Massey University, 2016)
Although leptospirosis is a disease of global importance, local context is crucial to formulating effective intervention strategies. Factors including reservoir host species, pathogen type, environmental, and social settings generate context-specific epidemiologies. Diverse climatic zones, agricultural systems, urbanization patterns, and cultural practices in Africa are likely to drive considerable variation in leptospirosis epidemiology. There is growing evidence of a substantial burden of human leptospirosis in Africa that is difficult to quantify in part due to lack of surveillance and clinical awareness of leptospirosis. Leptospirosis is therefore rarely considered as a differential diagnosis for acute febrile illness, and there is little access to diagnostic services for leptospirosis on the continent. In 2016, a virtual network was founded focussing on improving awareness and understanding leptospirosis in Africa. We currently have 40 members from academia, clinical practice, government and non-governmental agencies and others. Current members are based predominantly in institutions outside the continent but increasingly colleagues based in public health, laboratories, veterinary, and academic institutions within Africa are joining. We will share our experiences of developing this network, and our plans for capacity building through identifying and addressing knowledge gaps in our understanding of leptospirosis in Africa.